One size does not fit all: an analysis of the corruption preventative approach of the Anti-Corruption Commission (ACC) in Bangladesh. Issue 2 (4th May 2019) - Sakib, Nurul Huda
ABSTRACT: This paper argues that the global citizens' engagement movement against corruption does not always succeed in developing countries, such as Bangladesh. Drawing on the case of the preventative strategies of the Anti-Corruption Commission (ACC) in Bangladesh, this paper shows that government-driven citizens' engagement processes through community-based organisations (CBOs) are a ceremonial adaptation in response to isomorphic pressure from the donors. The outcomes from isomorphic pressure suggest that such donor-funded actions produce 'isomorphic mimicry' of successful corruption prevention programmes from other countries that do not succeed in the recipient country. A micro-level analysis based on interviews with stakeholders in Bangladesh demonstrates why isomorphic mimicry has failed to produce a robust anti-corruption prevention approach in Bangladesh.